Drug discovery research in Ghana, challenges, current efforts, and the way forward - Richard Kwamla Amewu; Patrick Amoateng; Patrick Kobina Arthur; Prince Asare; Isaac Asiamah; Daniel Boamah; Isaac Darko Otchere; Cedric Dzidzor Amengor; Edmund Ekuadzi; Kelly Chibale; Susan Jane Farrell; Regina Appiah-Oppong; et al. (Public Library of Science (PLoS), 2022)
We have a long-term vision to develop drug discovery research capacity within Ghana, to tackle unmet medical needs in Ghana and the wider West African region. However, there are several issues and challenges that need to be overcome to enable this vision, including training, human resource, equipment, infrastructure, procurement, and logistics. We discuss these challenges from the context of Ghana in this review. An important development is the universities and research centres within Ghana working together to address some of these challenges. Therefore, while there is a long way to go to fully accomplish our vision, there are encouraging signs.